The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1200/jco.2009.27.15_suppl.7079
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of imatinib resistance mutation analysis in chronic myeloid leukemia (CML) patients on imatinib at the time of loss of response to the drug in Asian Indian subjects

Abstract: 7079 Background: The treatment of (CML) has undergone major changes in the past decade with the introduction of tyrosine kinase inhibitors (TKI). However the initial enthusiasm is waning with increasing recognition of drug resistance. There is an urgent need to identify the types of receptor mutations which lead to drug resistance and their significance in salvage therapy. Methods: We identified 17 males and 8 female patients with median age 40 yrs (range 9–55 years) with CML who were on imatinib at the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Only 27 patients (27%) had mutation detected, M351T, T315I being most common in 4 patients each and F359I in 3 patients. Prakash et al [14] reported analysis of mutations in 25 patients with CML on Imatinib at the lime of loss of response to the drug in Asian-Indian patients. Twenty-two patients were in chronic phase and median age was 40 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 27 patients (27%) had mutation detected, M351T, T315I being most common in 4 patients each and F359I in 3 patients. Prakash et al [14] reported analysis of mutations in 25 patients with CML on Imatinib at the lime of loss of response to the drug in Asian-Indian patients. Twenty-two patients were in chronic phase and median age was 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…Kinase domain mutations were evaluated using the fluorescent nucleotide sequencing technique followed by bioinformatics tool, multiple nucleotide sequencing alignment. Indications of mutation analysis were based on recent European LeukemiaNet guidelines [14]. Loss of hematological response (HR), cytogenetic response (CyR) or molecular response or delay in attaining defined landmarks were indications for asking imatinib resistance mutation analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation